2020
DOI: 10.3390/jcm9041144
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of and Factors Associated with Balloon Adhesiolysis in Patients with Lumbar Post-Laminectomy Syndrome: A Retrospective Study

Abstract: Post-laminectomy syndrome (PLS) is characterized by chronic pain and complex pathological entity after back surgery. An epidural adhesiolysis is considered an effective treatment option for lumbar PLS. In this study, we retrospectively analyzed the outcome and evaluated the predictive factors of combined epidural adhesiolysis and balloon decompression using inflatable balloon catheters in lumbar PLS cases. One hundred and forty-seven subjects were retrospectively assessed and analyzed. The percentages of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In addition, as CT provides more information regarding the bone anatomy, such as calcification of bone spurs or intervertebral discs, than MRI, information that is essential for decompression surgery may actually be obtained [ 29 ]. Moreover, CT is a better alternative imaging method for patients with cardiac pacemakers who cannot undergo MRI for diagnostic purposes.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as CT provides more information regarding the bone anatomy, such as calcification of bone spurs or intervertebral discs, than MRI, information that is essential for decompression surgery may actually be obtained [ 29 ]. Moreover, CT is a better alternative imaging method for patients with cardiac pacemakers who cannot undergo MRI for diagnostic purposes.…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Indications for epidural steroid injections include acute radiating pain and neurological claudication that interfere with daily life, despite the administration of pain relievers and rest, which are anticipated to improve the symptoms. There are also reports of recent studies using epidural neuroplasty and other combination of drugs such as ropivacaine and dexmedetomidine related to thoracolumbar surgery [ 29 , 30 ].…”
Section: Nonoperative Treatmentmentioning
confidence: 99%
“…As the pain period is long, the accuracy of the pain duration decreases, which can be a factor that prevents accurate conclusions from being reached. In a similar preliminary study that reported that there was a correlation between pain duration and a decrease in pain score six months after the procedure when neuroplasty was performed in FBSS, the patient’s pain duration median value was 36 months [ 37 ]. Third, the research design was retrospective and had no control group, so there is a limitation that it can be influenced by other cofounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural steroid injection is indicated for acute radiating pain and nervous claudication that are interfering with daily life despite pain relievers and rest, which are expected to improve symptoms [45]. In addition, research on the use of ropivacaine and dexmedetomidine as well as epidural neuroplasty in conjunction with thoracolumbar surgery has been recently published [46,47]. Epidural neuroplasty is employed to alleviate back discomfort and/or radiating pain caused by mechanical compression of the intravertebral nerve structures or neuroinflammation.…”
Section: Epidural Steroid Injection and Othersmentioning
confidence: 99%